2013
DOI: 10.1542/peds.2012-2114
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Day-to-Day Lives of Obese Mexican-American Adolescent Females

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Obesity is a growing concern for Mexican-American adolescents, with both behavioral and cultural variables that are related to the increasing trend. WHAT THIS STUDY ADDS:These results highlight a patientcentered view of the emotional and physical burden of obesity in female Mexican-American adolescents, the families' personal struggles with weight-related conditions, and the challenge of balancing family needs with those specific to the adolescent. abstract OBJECTIVE: In an effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…17 Culture may also interact with the pressures of normal development to determine day-to-day lifestyle choices in minority youth. 18 Cultural norms change with both acculturation and globalization; however, these changes may differ by ethnic groups. For example, fruit and vegetable consumption is maintained in acculturated Asians but declines sharply among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…17 Culture may also interact with the pressures of normal development to determine day-to-day lifestyle choices in minority youth. 18 Cultural norms change with both acculturation and globalization; however, these changes may differ by ethnic groups. For example, fruit and vegetable consumption is maintained in acculturated Asians but declines sharply among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…Yet children with severe obesity have not been the focus of much research, especially research examining socioemotional correlates of obesity. Two exceptions are a study of ninety‐six 8‐ to 17‐year‐olds with severe obesity whose self‐reported victimization was related to loneliness and depression (Lim et al., ) and a qualitative study of 20 severely obese Mexican‐American female adolescents who reported problems with peer relations, including self‐isolation (Taylor et al., ).…”
Section: Social Life: School As An Interpersonal Context For Weight Pmentioning
confidence: 99%
“…[15][16][17] The few qualitative studies that have incorporated low-income families with an obese or overweight child have focused on barriers to making healthy lifestyle changes. 18,19 Yet few qualitative studies to date have identified factors that participants perceive facilitate the successful implementation of lifestyle changes.…”
mentioning
confidence: 99%